Obesity negatively impacts corneal nerves in patients with diabetes mellitus - Calesta Hui Yi Teo; Chang Liu; Mingyi Yu; Isabelle Xin Yu Lee; Ansa Anam; Ching-Yu Cheng; Yadana Htunwai; Jasmine Shimin Koh; Suresh Rama Chandran; Yu-Chi Liu (Eye and Vision)
Abstract Background To investigate the relationship between obesity and corneal nerve metrics in patients with type 2 diabetes mellitus (DM). Methods This cross-sectional study included a total of 385 healthy controls and 663 patients with DM. Metrics for corneal nerve and epithelial cells were evaluated using in-vivo confocal microscopy (IVCM). Corneal nerve and epithelial cell parameters were quantified and compared between patients with and without obesity and across six different body mass index (BMI) categories. Multivariable regression analyses were conducted to determine the association between corneal nerve metrics and BMI in patients with DM. Results Of the DM participants, 162 (25.4%) had obesity. Compared to the non-obese group, patients with obesity had significantly lower corneal nerve fiber density (CNFD, P < 0.0001), corneal nerve fiber length (CNFL, P = 0.002), and corneal nerve branch density (CNBD, P = 0.005). Analyses across different BMI categories showed a progressive decline in corneal nerve parameters including CNFD (P < 0.0001), CNFL (P < 0.0001), CNBD (P < 0.0001), corneal nerve fiber total branch density (P = 0.003), corneal nerve fiber area (P = 0.04), and corneal nerve fiber fractal dimension (P = 0.02) with increasing obesity severity. Multivariable regression analyses demonstrated that lower CNFD (β: − 0.21, 95% CI: − 0.29 to − 0.13, P < 0.0001), shorter CNFL (β: − 0.12, 95% CI: − 0.17 to − 0.07, P < 0.0001), and lower CNBD (β: − 0.17, 95% CI: − 0.30 to − 0.04, P = 0.01) were significantly associated with BMI after adjusting for confounders. There were no significant differences in the corneal epithelial parameters between the obese and non-obese groups. Conclusions General obesity, specifically higher BMI, adversely affects corneal nerve health in individuals with DM. Evaluation of corneal nerves and resultant keratopathy should be considered in patients with DM and concomitant obesity.